Keanekaragaman Serangga Musuh Alami Pada Pertanaman Kakao Di Kecamatan Leihitu Kabupaten Maluku Tengah - Hasinu, Jeffij V; Rumthe, Ria Y; Sarmin, Novianti (Universitas Pattimura, 2024)
The research aims to identify the types of natural enemy insects of cocoa fruit borer pests and analyze the diversity index and calculate the index of dominance of natural enemy insects in cocoa cultivation (Theobroma cacao L.) in Mamala and Hila Villages, Leihitu district, Central Maluku regency. Random sample method with sampling techniques with certain criteria (cocoa plants that have borne fruit). Each village was taken 3 farmers then each farmer determined 3 sample plots with a plot size of 20 x 20 m2 then determined 3 sample crops. Insect catching uses 4 traps namely sweep net, pit fall traps, yellow traps, and leaf traps. The dataanalyzed in the form of qualitative data is the type of insects found and quantitative data, namely the diversity index and the dominance index. Based on the results of the study obtained the results of the study obtained 5 orders and 9 Families that have the potential as natural enemies, namely the Order Hymenoptera, Dermaptera, Ortopthera, Diptera and Ordo Coleoptera while the Families found are the Family Formicidae, Chelisochidae, Carcinophoridae, Forficulidae, Mantidae, Dolichopodidae, Stratiomydae, Coccinelidae, and the Family Chrysomelidae. The natural enemy diversity index in mamala village cocoa plantation (0.0771) and Hila (0.0884) is low and the dominance index in Mamala (0.97600557) and Hila (0.97362747) is high